Tensile strength of bamboo fiber reinforced polymer / Nur Azrin Azlan - Azlan, Nur Azrin (2018)
In recent years, the natural fibers have attracted substantial importance as potential Synthetic Fiber Reinforced Polymer (SFRP). Therefore, the purpose of this study is to obtain tensile strength of Bamboo Fiber Reinforced Polymer (BFRP). In this paper, the optimum tensile strength of the BFRP was studied. Five samples of BFRP with different percentage of bamboo fiber were prepared starting from 2%, 4%, 6%, 8% and one control sample. Each of the samples were undergoes tensile testing for determination of tensile load. The results of optimum tensile stress and the optimum tensile load value of the tensile strength of the sample are determined from the result shown in the graph of maximum load versus extension at break. From the analysis, the optimum tensile load recorded was 1480.78N for the control sample (0% bamboo fiber). The BFRP sample with 6% bamboo fiber content was considered the best performance as it recorded the highest tensile load value which was 1241.94N when compared to 2%, 4% and 8% bamboo fiber content. There are several factors that affects the tensile load of BFRP such as the existence of the void, the fiber arrangement and the bonding between fiber and polymer.